Sleep restriction acutely impairs glucose tolerance in rats. Issue 12 (28th June 2016) - Jha, Pawan K.; Foppen, Ewout; Kalsbeek, Andries; Challet, Etienne
Abstract: Chronic sleep curtailment in humans has been related to impairment of glucose metabolism. To better understand the underlying mechanisms, the purpose of the present study was to investigate the effect of acute sleep deprivation on glucose tolerance in rats. A group of rats was challenged by 4‐h sleep deprivation in the early rest period, leading to prolonged (16 h) wakefulness. Another group of rats was allowed to sleep during the first 4 h of the light period and sleep deprived in the next 4 h. During treatment, food was withdrawn to avoid a postmeal rise in plasma glucose. An intravenous glucose tolerance test (IVGTT) was performed immediately after the sleep deprivation period. Sleep deprivation at both times of the day similarly impaired glucose tolerance and reduced the early‐phase insulin responses to a glucose challenge. Basal concentrations of plasma glucose, insulin, and corticosterone remained unchanged after sleep deprivation. Throughout IVGTTs, plasma corticosterone concentrations were not different between the control and sleep‐deprived group. Together, these results demonstrate that independent of time of day and sleep pressure, short sleep deprivation during the resting phase favors glucose intolerance in rats by attenuating the first‐phase insulin response to a glucose load. In conclusion, this study highlights the acute adverse effects of only a short sleep restriction on glucose homeostasis. Abstract : Short sleep deprivation affects glucose tolerance in rats. Basal levels of glucose, insulin, and corticosterone remain unchanged after sleep deprivation. Sleep deprivation impairs glucose tolerance tests by reducing the early‐phase insulin responses to a glucose challenge.